FINAL YEAR PROJECT: APPLICATION OF RFID UNIVERSITI TEKNOLOGI PETRONAS MAIN GATE. - A. GILBERT, JASON THADDEUS (IRC, 2019)
Universiti Teknologi PETRONAS practices the sticker system whereby cars that are parked in campus must be registered and a sticker will be given which is to be displayed on the front mirror. The security guards would manually check the cars as it is entering the main gate. The current system practiced faces issues such as it is time consuming and experiences data inconsistency which is caused by human error. This paper outlines a brief introduction of the RFID system, principles of the technology, problems encountered with the current system as well as the present and envisaged application of the RFID automation. Moreover, this system provides a solution to the problems faced due to its leveraged features which includes mutual authentication, security and access control, elimination of human error, wide scanning range and its ability to scan within milliseconds. This paper also justifies the used of RFID system is a huge leap forward in proper data management for UTP and how beneficial is the system towards the stakeholders of UTP. Every stakeholder with an authorized RFID card could enter the campus without wasting precious time. Furthermore, this system will push the security guards in checking thoroughly on unregistered vehicles entering UTP entrance, which leads to more secure environment inside UTP’s compound. This RFID technology can be implemented at the entrance of the faculty to provide more width and possibilities of this technological era.